TGF-β: A novel predictor and target for anti-PD-1/PD-L1 therapy - Ming Yi; Ming Yi; Tianye Li; Mengke Niu; Yuze Wu; Zhenyu Zhao; Kongming Wu (Frontiers in Immunology, 2022)
Transforming growth factor-β (TGF-β) signaling regulates multiple physiological processes, such as cell proliferation, differentiation, immune homeostasis, and wound healing. Besides, TGF-β plays a vital role in diseases, including cancer. Accumulating evidence indicates that TGF-β controls the composition and behavior of immune components in the tumor microenvironment (TME). Advanced cancers leverage TGF-β to reshape the TME and escape immune surveillance. TGF-β-mediated immune evasion is an unfavorable factor for cancer immunotherapy, especially immune checkpoint inhibitors (ICI). Numerous preclinical and clinical studies have demonstrated that hyperactive TGF-β signaling is closely associated with ICI resistance. It has been validated that TGF-β blockade synergizes with ICI and overcomes treatment resistance. TGF-β-targeted therapies, including trap and bispecific antibodies, have shown immense potential for cancer immunotherapy. In this review, we summarized the predictive value of TGF-β signaling and the prospects of TGF-β-targeted therapies for cancer immunotherapy.